Hypoxia in cardiogenesis of rats - Kobeza, P.A. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Hypoxia during early stages of cardiogenesis in rats causes complications in the functional development of cardiomyocytes. Cardiogenesis under hypoxia refers to the process of generating new cardiac cells or cardiomyocytes in response to low oxygen levels or hypoxia. This process occurs as a means of adaptation of the heart to support its function in conditions of reduced oxygen supply. Hypoxia can activate certain signaling pathways such as the hypoxia-inducible factor (HIF) pathway. Objective. To determine hypoxia as a general complicated state. To identify factors that cause this condition. To provide a characterization of complications and ways of their progressive development in different regions of the heart during early ontogenesis. Understanding the causes and mechanisms of hypoxia is crucial for developing effective methods of detecting this pathological and functional state of myocardial cells in rats. Methods. Systematic literature review, meta-analysis, content analysis. Results. The main types of hypoxia and their influence on the structure and development of rat myocardium are presented. The process of development of myofibrils and mitochondria in different zones of the myocardium during ontogenesis is described in detail. Conclusions. The use of histological methods on animal models can provide an understanding of the mechanisms underlying cardiogenesis under hypoxia and can help in developing effective methods of diagnosing the effects of low oxygen levels on the process of formation of cardiac muscle tissue.